A gestão da educação pública em Palmas de Monte Alto: do ordenamento às ações na escola (2005-2015) - Rocha, Marilene Pinto Cardoso Laranjeira (2021)
Since the 1990, in Brazil, the administration of education has been polarized around the idea of a "new model" of public administration, called management, defended by sectors aligned with the liberal matrix movements, which question the state's role as much in controlling the economy as in promoting social agendas. The realization of this study permeates, therefore, the complex challenge of to think about the administration of education in this context, illuminating the relationships between trends global policies and their implications in regional spaces. In this sense, this work researched the administration of public education in Palmas de Monte Alto in the period (2005-2015), with the following question: what are the conceptions and democratic management mechanisms are presented in the planning of education in the municipality of Palmas de Monte Alto and how they present themselves in the performance of teachers, pedagogical coordinators and school managers? The research had as its general objective to characterize and analyse the relations among the constitutional principle of Democratic Management, the adequacy movements of the municipal education system Palmas de Monte Alto and its repercussions on the performance of school managers, pedagogical coordinators and teachers, observing the conceptions of management in discussion. Three central categories were the reference of analyses in a historical-critical conception: democracy, participation and democratic management. The category democracy was instrumental in helping to understand the socio-political context and educational, since it is a polysemic term that (re)configures itself at different times and spaces and can substantially interfere with education and management conceptions. The participation category measured the understanding and analysis of local policy; finally, the democratic management category has enabled us to understand the relationship between political choices and the ways of conducting the management of the municipality's education system, including school management. As for methodological paths, the choice was made to qualitative research, with the use of semi-structured interviews and the analysis of documentary tools for information collection. For data interpretation document .The data pointed to the current use of the principle of democratic management in official actions, including in the subjects' statements and in the documents produced, however they revealed tensions, dissenities and disputes over different projects of education and society. In the school environment, there was the circulation and influence of different management approaches, which do not always result from the understanding of political senses associated with specialized literature. The participating subjects pointed out the difficulties in advancing in the consolidation of democratic management at school due to its space condition that reflects social practices in movement and, therefore, strongly influenced by dominant political trends. Thus, the democratic education project still lives with the gap between theory and practice in terms of participation in the school context.